Tuina for treatment of atopic eczema in children under 14 years: A systematic review of randomized controlled trials - Chunli Lu; Xinyan Jin; Darong Wu; Sijia Zhu; Lily Lai; Jianping Liu (Journal of Traditional Chinese Medical Sciences, 2019)
Objective: Due to a lack of available effective treatments for atopic eczema (AE), non-pharmaceutical therapy such as Tuina has been frequently sought after as an alternative treatment. We evaluated the benefits and harms of Tuina for children with AE under 14 years of age. Methods: We searched for randomized controlled trials (RCTs) on Tuina in seven Chinese and English databases from their inception to June 2018. We included children under 14 years of age with AE received Tuina alone or combined with conventional medicine. Two authors independently extracted data and used the Cochrane “Risk of bias” tool to assess the methodological quality. Effects were presented as relative risk with 95% confidence interval using RevMan 5.3. Data not suitable for statistical pooling were synthesized qualitatively. Results: Nine RCTs involving 1246 children with AE were included. The trials were at unclear or high risk of bias. Tuina manipulation in each trial was different. Compared to usual care, three trials showed greater effects of Tuina alone or combined with usual care for global symptoms and signs improvement, such as itching, and skin lesions. Four trials showed that Tuina had ≥50% improvement in symptoms and signs. Due to clinical heterogeneity, meta-analysis was not possible. At follow-up of between 4 weeks and 6 months, five trials of Tuina alone or Tuina combined with usual care showed lower rates of relapse compared to usual care alone. Four trials reported no occurrence of severe adverse events. Conclusions: Limited evidence demonstrates that Tuina may improve symptoms and signs of AE and reduce relapse rate in children <14 yrs with AE. Tuina is generally acceptable in these trials. Further well-designed RCTs are warranted to confirm these benefits and to explore safety further. Keywords: Tuina, Atopic eczema, Non-pharmaceutical therapy, Pediatrics, Systematic review